Speckle metrology - Sirohi, Rajpal S. (Optical engineering (Marcel Dekker, Inc.), 1993)
This practical reference offers state-of-the-art coverage of speckle metrology and its value as a measuring technique in industry.;Examing every important aspect of the field, Speckle Metrology: surveys the origin of speckle displacement and decorrelation; presents procedures for deformation analysis and shape measurement of rough objects; explains particle image velocimetry (PIV), the processing of PIV records, and the design requirements of PIV equipment; discusses the applications of white light speckle methods and the production of artificial speckles; describes the measurement of surface roughness with laser speckles and polychromatic speckles; illustrates semiautomatic and automatic methods for the analysis of Young's fringes; calculates the variation of Young's fringes with the change in the microrelief of the rough surface; and explicates hololenses for imaging and provides design details with aberration corrections for hololense systems.;With over 1500 literature citations, tables, figures and display equations, Speckle Metrology is a resource for students and professionals in the fields of optical, mechanical, electrical and electronics engineering; applied physics; and stress analysis.